30‐4: Semantic Simultaneous Localization and Mapping for Augmented Reality. Issue 1 (30th May 2018) - Yu, Bing; Li, Yang; Chen, Chao Ping; Maitlo, Nizamuddin; Chen, Jiaqi; Zhang, Wenbo; Mi, Lantian
Abstract : We propose a semantic SLAM for augmented reality, which combines SLAM‐based navigation and YOLO‐based object detection. Our solution is able to simultaneously create sparse map points and annotate them with detected objects. Our experiments are implemented with Nvidia's GTX 1080Ti on KITTI's datasets.